Use of vinasse, an ethanol distillery waste, as an amendment to bioremediation of diesel oil contaminated soils - Mariano, Adriano Pinto [UNESP]; Crivelaro, Sérgio Henrique Rezende [UNESP]; De Angelis, Dejanira De Franceschi; Bonotto, Daniel Marcos (My University, 2006)
This work investigated the possibility of using vinasse as an amendment in bioremediation processes by supplying nutrients and as an extra labile carbon source that could increase the microorganisms population. Soil samples were collected at three petrol stations. At two of them, diesel oil spills occurred from underground storage tanks and at the third, samples were collected during the replacement of underground pipes and it was simulated a diesel oil contamination by adding diesel oil purchased from a local petrol station or weathered diesel oil collected from the groundwater of a petrol station. Batch biodegradation experiments were carried out in Bartha biometer flasks that were used to measure microbial CO2 production. Biodegradation efficiency was also measured by quantifying the total petroleum hydrocarbons (TPH) by gas chromatography. Although certain fertilization of the soil and an increase of the microbial population were obtained with the vinasse, in the studied conditions, it demonstrated to not be adequate to enhance the bioremediation efficiency of diesel oil contaminated soils.
Keywords: Bioremediation; Diesel oil and vinasse; Soil